Extending the magnetic order of MnAs films on GaAs to higher temperatures - Ney, A; Hesjedal, T; Daweritz, L; Koch, R; Ploog, K (2005)
Manganese arsenide is a promising candidate for new spintronics applications since it is ferromagnetic at room temperature and can be grown with high epitaxial quality on semiconductors. However, the transition temperature of ∼40 °C is a limiting factor for device applications. Since the coupled magnetic and structural transition is of first order, it is in principle possible to shift the transition temperature by changing external parameters. Here we show that by either applying an external magnetic field or by growing the MnAs films on GaAs(1 1 1), i.e., by changing the epitaxial constraints which are equivalent to external pressure, ferromagnetic order can be stabilized well above the bulk-phase transition temperature. © 2004 Elsevier B.V. All rights reserved.